Integrated decision support system for human resource selection using TOPSIS based models - Wan Suryani, Wan Awang; Fadhilah, Ahmad; Syadiah Nor, Wan Shamsuddin (Hikari Ltd., 2015)
Among the responsibilities of Human Resource Department is selecting the right people for the available job. This task tends to be the most challenging due to necessity to make tough decisions under uncertainty. To minimize error occurrences and complexity of the selection process, Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) method is adopted together with fuzzy TOPSIS and Fuzzy set theory to provide solutions to Multi-criteria decision making (MCDM) problems associated with human resource selection (HRS) process. The proposed framework of Integrated Decision Support System for Human Resource Selection using TOPSIS based models was constructed and presented in this paper.